Microorganism of public health significance in newly prepared balao-balao (unfermented balao-balao). - Ferrer, Sonia D. (College of Fisheries, University of the Philippines, 1981)
Commercial samples of balao-balao from three different sampling stations in Bacolor, Pmapanga were studied as to their initial microbial load of microorganisms of public health significance. Microorganisms under the study included the determination of coliforms, staphylococcus aureus and salmonella. Microbial examination was done using the most probable number of Coliforms; enumeration of coagulase positive staphylococcus aureus; enumeration of salmonella by the most probable number method. Readings for initial pH were also recorded for the samples. Determination studies were done on newly prepared balao-balao. Microbial examination showed the presence of S. aureus and salmonella in one of the three sampling stations. The average number obtained for S. aureus was 2x10^1/g, while for salmonella was 3x10^2/g. the study showed that coliforms were the prevalent contaminants among the three, the value ranging from 10^1 to 10^4/g. generally, surface samples were shown to contain more of these organisms than the bottom samples. Average initial pH value for the three sampling stations is 7.02, which is favorable for the growth of these microorganisms in the still unfermented mixtures.